2008
DOI: 10.1080/13880200701739413
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Activity of the Red AlgaPolysiphonia virgata.

Abstract: The red marine alga (Polysiphonia virgata C. Agardh; Rhodomelaceae) was investigated for antimycobacterial activity. Bioassay-guided fractionation of the dichloromethane algal extract using direct bioautography resulted in isolation of a mixture of long-chain fatty acids, namely oleic acid, linoleic acid, lauric acid, and myristic acid as the major antimycobacterial compounds. Oleic acid showed the greatest inhibition of the growth of Mycobacterium smegmatis with a minimum inhibitory quantity (MIQ) of 0.8 µg; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 43 publications
2
13
0
1
Order By: Relevance
“…This result agrees with the report of Khotimchenko and Vaskovsky who suggested that fatty acids are a vital constituent of both terrestrial and marine plants [73,74]. The immunostimulation observed in the present study might be due to phytoconstituents of S. wightii which include palmitoleic acid, n-hexadecanoic acid, oleic acid, octadecanoic acids, cis-13-octadecenoic acid and cyclooctaneacetic acid.…”
Section: Discussionsupporting
confidence: 82%
“…This result agrees with the report of Khotimchenko and Vaskovsky who suggested that fatty acids are a vital constituent of both terrestrial and marine plants [73,74]. The immunostimulation observed in the present study might be due to phytoconstituents of S. wightii which include palmitoleic acid, n-hexadecanoic acid, oleic acid, octadecanoic acids, cis-13-octadecenoic acid and cyclooctaneacetic acid.…”
Section: Discussionsupporting
confidence: 82%
“…Coughs, chest ailments, fever (Watt and Breyer-Brandwijk, 1962;Bryant, 1966;Hutchings et al, 1996;Mativandlela et al, 2008) Bark Alkaloids (Dictionary of Natural Products, 1996) Ethanol extract of leaves not active (Mycobacterium smegmatis and Mycobacterium tuberculosis) (Mativandlela et al, 2008) Rhodomelaceae Polysiphonia virgata C. Agardh --Fatty acids (Saravanakumar et al, 2008) Fatty acid mixture active (Mycobacterium smegmatis and Mycobacterium tuberculosis) (Saravanakumar et al, …”
Section: Loganiaceaementioning
confidence: 98%
“…Commercial standards of these fatty acids were obtained for subsequent analysis. Oleic acid was the most active against Mycobacterium smegmatis, with a minimum inhibitory quantity (MIQ) obtained using direct bioautography of 0.8 g, while linoleic and lauric acids had MIQ values of 1.56 and 3.13 g, respectively (Saravanakumar et al, 2008). Against Mycobacterium tuberculosis H 37 Rv in the BACTEC method, oleic acid was 100% inhibitory at a concentration of 25 g/ml, and lauric, myristic and linoleic acids showed 98-100% inhibition at 50 g/ml (Saravanakumar et al, 2008).…”
Section: Biological Activity Screening Of Plant Extracts For Antimycomentioning
confidence: 99%
See 1 more Smart Citation
“…Dodecanoic acid (lauric acid) and its derivatives have found to possess antibacterial (Rouse et al, 2005), antifungal (Rihakova et al, 2001), antitumour (Kato et al, 1971), anti-inflammatory (Calder and Grimble, 2002), antimycobacterial (Saravanakumar et al, 2008) and antiviral (Villamor et al, 2007) activities.…”
Section: Introductionmentioning
confidence: 99%